Inferential control of fatty acid fractionation column - Lim, Wan Piang; Ahmad, Arshad (Penerbit Universiti Sains Malaysia, 2004)
Nowadays, chemical production is moving towards full capacity operation with high profitability while aiming to achieve zero accidents and zero emissions. Process control and monitoring is amongst the important factors that will help to accomplish these targets. Successful implementation of process control in operating plant requires relevant control strategies with reliable on-line measurement. However, difficulties in on-line measurement for some product qualities still exist due to large time delay, low sampling rate, high cost and unavailability of soft sensors. Recently, inferential control has been considered as a good strategy to deal with the limitations.